The Skype Application for Lecture Solutions Reading for Professional Context During Pandemic - Sari, Ambar Wulan; Arifin, Muhammad; Amalia, Nadra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Online learning method based on distance education through the Skype application in the Reading for Professional Context course. where the state of research during a pandemic is very important to find easy and appropriate ways and achieve learning objectives. Researchers are interested in further researching online learning methods based on distance education through the Skype application in the Reading for Professional Context course in the English Education Study Program so that the competency standards of the courses can be implemented and run in an orderly, innovative and active manner, especially can be practiced online even though without studying in class students remain enthusiastic about attending lectures. Research planning, to be able to find out the results of the application of distance education-based online learning methods through the Skype application in the Reading for Professional Context course is to analyze student behavior and test this learning online.